A Revised Writer(s)-Within-Community Model of Writing. Issue 4 (2nd October 2018) - Graham, Steve
Abstract : This article presents a revised version of the writer(s)-within-community model of writing. Writing is conceptualized as a social activity situated within specific writing communities. Writing in these communities is accomplished by its members. The model proposes that writing is simultaneously shaped and bound by the characteristics, capacity, and variability of the communities in which it takes place and by the cognitive characteristics, capacity, and individual differences of those who produce it. The model further proposes that writing development is a consequence of participation in writing communities and individual changes in writers' capabilities, which interact with biological, neurological, physical, and environmental factors. This newer version of the model places a greater emphasis on communication and the reader. It expands the description of a writing community to include the social, cultural, political, institutional, and historical influences that shape it. It further describes the tenets that underlie the operation of the model.